Розрахунок ймовірності дискретних станів системи із п'ятьма одиницями збиральної техніки - Ковальчик, Ю. І.; Говда, О. І. (НТУ "ХПІ", 2016)
Застосовано підхід, заснований на положеннях теорії випадкових марківських процесів, до визначення ефективності функціонування систем із дискретними станами, зокрема, для визначення імовірності відповідних станів, у яких може перебувати система. Розглянуто приклад системи, складеної з п‘яти одиниць збиральної техніки. Сформульовано задачу Коші для системи диференціальних рівнянь. Розраховано ймовірності перебування системи у дискретних станах.

The given article is dedicated to the improvement of determination method of the efficiency of functioning of the system with discrete states. It is offered the application of Markov processes for the determination of appropriate states probability, in which the system can be. The model example is considered. In particular, the system composed of five units of harvesting techniques is considered. For this the system of differential equations. The intensities of events flow appear in the system. They cause the rejection of unit i of harvesting techniques and the intensities of events flow after ―finishing of repairing‖ of unit i of harvesting techniques. The intensities of rejections as time function are considered. The system is solved using numerical methods. The probabilities of finding the system in the discrete states are calculated. The graphs are given. It is shown how the probabilities of states depending on time change.
Calculating the probability of discrete states of a system with five units harvesting machinery
Keywords: управління проектами; марківський процес; рівняння Колмогорова; добова продуктивність комбайна; project management; Markov processes; discrete states; Kolmogorov‘s equations